THIRTEEN WAYS OF LOOKING AT AN ALGORITHM: HOW JOURNALISM FRAMES THE DISRUPTIVE POTENTIAL OF GENERATIVE AI - Kessler, Fritz; Ponniah, Gabriel; Butkowski, Chelsea; Sinnreich, Aram; Aufderheide, Patricia (AoIR Selected Papers of Internet Research, 2026)
In this article, we aim to identify and trace some of the most prevalent frames andtropes surrounding GAI, examining how dominant media outlets–national news mediaand professional trade publications–framed and discussed generative AI, particularly inrelation to education and media production, during the first year of GAI’s widespreadrollout, from November 2022-October 2023.We employ framing analysis for its focus on how journalists’ understanding of emergingtechnologies shapes news coverage, which ultimately informs public opinion (D’Angelo,2017; Tewksbury & Scheufele, 2009). Our emergent frames were developed usingqualitative discourse analysis (Fairclough, 2010), recognizing that initial media coverageof an emerging social issue or technical regime serves as a proxy to understandbroader public understanding, within key professions, of issues and problemssurrounding the widespread adoption of new technologies.Once we developed our emergent taxonomy of common frames, we employed a novel,GAI-based technique for framing analysis. We used iterative prompt engineering onopen source LLM DeepSeek to investigate not only the discursive frameworks but alsothe emotionally valent (positive vs. negative) subframes included in each news article,taking care to validate its outputs through intercoder reliability testing.